What does the quantitative morphological diversity of starch grains in terrestrial orchids indicate?. Issue 8 (9th May 2022) - Süngü Şeker, Şenay
Abstract: Starches granules vary in structure and morphologies in the orchids as well as other plant sources that starch is industrially valuable. This article aims to provide information on the variability of starch grain based on quantitative size and shape descriptive features using regression and discriminant analysis and to develop an easy method related to starch morphology giving perspective for various disciplines. All measurements of 26 species belonging to three different tribes were obtained using polarized light and scanning electron microscopy. Results show significant differences in size descriptive (e.g., perimeter, the major axis of the fit ellipse, minimum caliper diameter) and shape descriptive (e.g., circularity, hilum position) features, suggesting that taxonomic assignment of orchids starch granules to a higher category could enable to the testing of the industrially desired product and protect orchid biodiversity. Highlights: Studies on detailed morphology and morphometry of orchid starch using polarized light microscopy and scanning electron microscopy. Relation and effect of size descriptive on shape descriptive features (circularity and hilum position) of the starch grains. Described size and shape pattern of starch granules, and confirmed the usefulness of quantitative data sets for easily and effectively assessing the variation of the orchid. Abstract : Qualitative and quantitative starch grain morphology.